2020
DOI: 10.3846/tede.2020.13997
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Credit Scoring Model Based on Survival Gradient Boosting Decision Tree Approach

Abstract: Credit scoring, which is typically transformed into a classification problem, is a powerful tool to manage credit risk since it forecasts the probability of default (PD) of a loan application. However, there is a growing trend of integrating survival analysis into credit scoring to provide a dynamic prediction on PD over time and a clear explanation on censoring. A novel dynamic credit scoring model (i.e., SurvXGBoost) is proposed based on survival gradient boosting decision tree (GBDT) approach. Our proposal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Xia Y and other scholars proposed a SurvXGBoost model based on the Gradient Boosting Decision Tree (GBDT) method, and applied it to the consumer loan dataset. The performance is excellent [11].…”
Section: Related Workmentioning
confidence: 99%
“…Xia Y and other scholars proposed a SurvXGBoost model based on the Gradient Boosting Decision Tree (GBDT) method, and applied it to the consumer loan dataset. The performance is excellent [11].…”
Section: Related Workmentioning
confidence: 99%
“…Ensemble credit scoring models are mainly established by bagging, boosting or stacking algorithms (He et al, 2018;Xia et al, 2018a). Bagging artificial neural network (Tsai & Wu, 2008), random forests (RF) (Tang et al, 2019), GBDT (Xia et al, 2021a;Xia et al, 2017b), and heterogeneous ensemble models (Schotten & Morais, 2019) are typical applications of ensemble credit scoring models. The empirical results also demonstrate the advantages of ensemble models (Lessmann et al, 2015).…”
Section: Modelling Approaches Of Credit Scoringmentioning
confidence: 99%
“…They concluded that the XGBoost with DNN provides comparatively better performance relative to certain other widely used techniques and methodologies. Based on the survival gradient boosting decision tree (GBDT) approach, Xia et al 10 proposed a novel dynamic credit scoring model, SurvXGBoost. The authors combined the GBDT and survival analysis approach.…”
Section: Background and Previous Workmentioning
confidence: 99%